Social Identities of Children in different Institutional Contexts - Højlund, Susanne (Outlines. Critical Practice Studies, 2001)
Based on an ethnographic fieldwork the article analyses the experiences of 8-10 year old children in three different institutions. It is shown how the children create and maintain different social landscapes in each setting. This means that children's experiences are related to the position they have in the landscape. The notion social identity is used to discuss and explain these findings. With this notion identity is explained as an interplay between internal and external factors: between group-identification and categorisation. Children's different identities in different settings are not created by children themselves, but must bee seen in relation to the categorisation used by the adults to classify children. The professional categorisations of children are a central part of the social space in relation to which children act, talk, and play.